2003
DOI: 10.1590/s1413-78522003000200003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methylprednisolone in medullar injury in rats: a functional and histological analysis

Abstract: The pharmacological effects of the methylprednisolone in the treatment of the spinal cord lesion, have been researched. An experimental study was performed with twelve wistar rats subjected to a contusion lesion of the spinal cord, by the NYU system. The rats were divided in two groups; the MP group which received the methylprednisolone after the contusion lesion and the control group, which received a 0,9% physiological serum. An analysis of the recuperation of the functional movement of the rats was accompli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…In animal models, clinical improvement with corticoids is not necessarily followed by recovery of histological damage [34]. For example, Merola et al [35] observed no change in GFAP expression in adult rats with complete spinal cord injury receiving methylprednisolone.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, clinical improvement with corticoids is not necessarily followed by recovery of histological damage [34]. For example, Merola et al [35] observed no change in GFAP expression in adult rats with complete spinal cord injury receiving methylprednisolone.…”
Section: Discussionmentioning
confidence: 99%